2010
DOI: 10.1136/qshc.2010.042077
|View full text |Cite
|
Sign up to set email alerts
|

The quality of clinical practice guidelines over the last two decades: a systematic review of guideline appraisal studies

Abstract: This review shows that despite some increase in quality of CPGs over time, the quality scores as measured with the AGREE Instrument have remained moderate to low over the last two decades. This finding urges guideline developers to continue improving the quality of their products. International collaboration could help increasing the efficiency of the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
380
2
38

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(472 citation statements)
references
References 60 publications
52
380
2
38
Order By: Relevance
“…There is existing scientific evidence to support improved outcomes when guidelines that have been rigorously evaluated are adopted in clinical practice [14]. Despite an increasing volume of guidelines in clinical medicine during the last two decades, some studies have reported gross failings in their methods and little improvement in quality with time [3,4,26]. Clinician concern regarding the quality of guidelines may contribute to poor uptake and this potentially hinders improvements in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…There is existing scientific evidence to support improved outcomes when guidelines that have been rigorously evaluated are adopted in clinical practice [14]. Despite an increasing volume of guidelines in clinical medicine during the last two decades, some studies have reported gross failings in their methods and little improvement in quality with time [3,4,26]. Clinician concern regarding the quality of guidelines may contribute to poor uptake and this potentially hinders improvements in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…12,[26][27][28] La publicación de GPC incompletas, incluso con carácter oficial, es un problema básico y, desafortunadamente, en mayor o menor medida, global. El dominio de "rigor en la elaboración", se considera medular en las guías, ya que demuestra la realización de búsquedas exhaustivas de evidencia, no sesgadas y reproducibles.…”
Section: Discussionunclassified
“…[8][9][10] Evaluar integralmente las GPC, especialmente en programas oficiales como el implementado sectorialmente en México, 11 debería incluir componentes para cada etapa del proceso. Sin embargo, lo común es realizar evaluaciones parciales: ya sea valorar la presencia de atributos de la calidad formal de las GPC, 12 las estrategias y barreras para su implementación 10,13 o en el grado de cumplimiento de sus recomendaciones.…”
Section: Salud Pública De México / Vol 59 No 2 Marzo-abril De 2017unclassified
“…Este instrumento es la herramienta más ampliamente usada para la evaluación de las GPC y ha sido utilizada en por lo menos 42 estudios de 626 GPC durante los últimos 20 años 23 . Recientemente se ha publicado una nueva versión del instrumento -el AGREE II-que mejora algunos problemas identificados previamente y que está comenzando a ser utilizada por los investigadores en el área 24 .…”
Section: Elaboración De Gpcunclassified